Elder Nutrition - Linda B. Bobroff; Martie Gillen (EDIS)
Good nutrition is important throughout life, starting even before we are born. However, at certain stages in life, such as infancy, pregnancy, and in older age, the importance of having good eating habits is especially critical. This revised 8-page fact sheet focuses on how aging affects nutrition and diet and choices that older adults can make to improve or maintain their health and well-being as they age. Written by Linda B. Bobroff and Martie Gillen, and published by the UF Department of Family, Youth and Community Sciences, April 2014.